2013
DOI: 10.1186/1471-2407-13-522
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A7 suppresses lymph node metastasis of hepatocarcinoma cells in a mouse model

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the leading causes of cancer death in China. This study investigated the effects of Annexin A7 (ANXA7) on the inhibition of HCC lymph node metastasis in a mouse model.MethodsThe stable knockup and knockdown of Annexin A7-expressing HCC cells using Annexin A7 cDNA and shRNA vectors, respectively, were injected into a mouse footpad to establish primary and metastatic tumors in mice. On the 14th, 21st, and 28th days after HCC cells inoculation, the mice were sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Recently, we found CRKL was linked to the lymphatic metastasis of hepatocarcinoma [23]. Using murine hepatocarcinoma Hca-P cell line, an ideal cell line for mimicking the initial (low) and specific lymph node metastasis (LNM) of hepatocarcinoma in vitro and in vivo [2,4,[23][24][25][26][27][28], we found CKLP overexpression effectively inhibits the in vitro proliferation, migration and invasion capacities of Hca-P cells [23]. Herein, the potential tumor suppressor role of CRKL in Hca-P was further validated by RNAi silencing combined with in vitro proliferation, migration and invasion assays and with in vivo tumorigenicity and LNM rate and level determinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found CRKL was linked to the lymphatic metastasis of hepatocarcinoma [23]. Using murine hepatocarcinoma Hca-P cell line, an ideal cell line for mimicking the initial (low) and specific lymph node metastasis (LNM) of hepatocarcinoma in vitro and in vivo [2,4,[23][24][25][26][27][28], we found CKLP overexpression effectively inhibits the in vitro proliferation, migration and invasion capacities of Hca-P cells [23]. Herein, the potential tumor suppressor role of CRKL in Hca-P was further validated by RNAi silencing combined with in vitro proliferation, migration and invasion assays and with in vivo tumorigenicity and LNM rate and level determinations.…”
Section: Discussionmentioning
confidence: 99%
“…Its overexpression in Hca-P, an initial (low) and specific lymph node metastasis (LNM) murine hepatocarcinoma cell line [2,4,[23][24][25][26][27][28], suppresses the in vitro proliferation, migration and invasion abilities of Hca-P cells. In current work, we continuously validated the potential tumor suppressor role of Our previous study (Biomed Pharmacother 2015;69:11) demonstrated that the over-expression of CRKL, a chicken tumor virus number 10 regulator of kinase-like protein, suppresses in vitro proliferation, invasion and migration of murine hepatocarcinoma Hca-P cell, a murine HCC cell with lymph node metastatic (LNM) rate of $25%.…”
Section: Introductionmentioning
confidence: 99%
“…shRNA knock down of Ech inhibited the proliferation, and decreased the adhesion and migration capacities of Hca-F cells; correspondingly, its overexpression in Hca-P cells promoted proliferation, and increased adhesion and migration capacities [37]. Moreover it was also found up-regulated in human hepatocellular carcinoma tissues compared to normal liver tissues by IHC [39].…”
Section: Hepatocarcinomamentioning
confidence: 91%
“…[37][38][39][40][41] Tumor angiogenesis is an important process and pathway that metastatic tumor tissue changes from a state difficult to observe with naked eyes into a state with obvious tumor metastasis. [30] Nowadays, compounds screened to inhibit tumor angiogenesis are provided with antitumor metastasis effects.…”
Section: Cell Motility and Tumor Angiogenesismentioning
confidence: 99%